Uso do tema gerador "solos" para uma prática metodológica interdisciplinar no ensino de química - Sivico, Mayki Jardim (2021)
The search for contextualization leads the teacher to develop methodologies that aim to enhance student learning in the classroom. Interdisciplinarity in Basic Education reflects a need to male knowledge more integrative in the school environment, and it is essential to use an increasingly broad dialogue between the disciplines in this process. The aim to intertwine the historical and cultural perspective developed by Levi S. Vygotsky , whit the use of the generating themes in Basic Education that are explained by Paulo Freire Through this dialectic process. This research is based on these theoretical fronts, with the objective of analyzing the potentialities of developing an interdisciplinary methodological practice, involving the subjects of Geography and Chemistry, from the generating theme “soils” with a 1st grad high school class of a state public school, in the city of Nova Venécia (ES). This research is classified according to Antonio C. Gil, as qualitative of the type participant. The elaboration and development of the project with the students are based on the three pedagogical moments outlined by Demetrio Delizoicov, José A. Angotti and Marta. M. Pernambuco. The initial stage is the realization of the collective planning by teachers of Geography and Chemistry, for the classes of 1 st and 2nd grades of high school. The second stage discusses the development of the project with the 1st grade class, based on the contents guided on the land relief and soil management and conservation practices in the discipline of Geography and the acid and basic character of chemical substances, involving the practical concept of pH in the discipline of Chemistry. It involved the students in the realization of experimental activities, field research, presentation of seminars, besides the realization of a focal group at the end of the project. The analysis of the results is based on a qualitative description of the moments experienced, and by means of the inductive method makes it possible to bring some perceptions and reports in a more dialogical way. The discussions concerning the focal group demand the categorization process, through the analysis of content described by Laurence Bardin. The analysis of the research discuss the importance of interdisciplinary collaborative work in the school, as well as to guide some reflections about the challenges and contributions to the Teaching of Chemistry, in order to bring this reflection of the interdisciplinary attitude as a potentiality in the school environment. Through the categories brought the reflection of the need to bring to the student methodologies that protagonize their learning, bringing the student as a critical and reflective subject. Finally, it is considered that by using the theme generator soils, it has allowed the students to see other opportune ways to learn chemistry, and through this process focused on interdisciplinarity, it allows knowledge to expand beyond the school walls.